Transforming your STEM career through leadership and innovation inspiration and strategies for women - McCauley-Bush, Pamela (Elsevier/Academic Press, 2013)
"Transforming Your STEM Career Through Leadership and Innovation offers valuable information on what it means to be a leader and innovator and encourages you to discover and develop these skills for yourself. This book integrates leadership and innovation principles with personal examples and profiles of inspirational women. By providing a clear process on how to build upon your personal strengths to realize leadership and innovation goals, this book will inspire you to pick up the mantle and meet the critical need for leadership and innovation in the STEM fields. This is a must-have guide that is relevant and valuable for women in all stages of their careers"--Provided by publisher.